Influence of hormone replacement therapy on the level of alkaline phosphatase and acid phosphatase in serum and saliva among women with estrogen deficiency - Rahnama, Mansur; Jachewicz, Tomasz; Łobacz, Michał; Czajkowska, Wioletta; Stelmaszczyk, Marcin (Menopause Review/Przegląd Menopauzalny, 2012)
To alleviate the adverse effects resulting from the cessation of ovarian endocrine function, menopausal women use more and more often hormone replacement therapy (HRT). This article aims to assess the impact of HRT on bone tissue, by determining the total level of alkaline phosphatase and acid phosphatase. The study included 120 women in the menopausal period, of which 60 received hormonal treatment. The control group comprised 60 women not using HRT. The tested material was the unstimulated saliva and venous blood collected in a fasting state. The material was centrifuged to obtain supernatant (saliva) and serum (blood) and stored until the testing at –70°C. Statistically significant differences in the level of both enzymes in the blood of both groups of patients were obtained. In saliva, the differences were not statistically significant.